Decadal remote-sensing analysis of eutrophic indication in the Spermonde Islands, Indonesia - Ahmad Faizal (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2022)
The trophic level of marine waters is closely related to the high concentration of nutrients in the water column. One of nutrient indicators is the concentration of chlorophyll-a. The research aims to map the decade of change in Spermonde waters' status with the indicator of chlorophyll-a by utilizing remote sensing technology. The research method used the digital image processing for the analysis of chlorophyll-a concentrations. Data distribution were plotted with kriging techniques and the trophic level was classified based on the Hakanson method. The results showed that there was a change in the trophic level of the Spermonde Islands in 1996-2020. Mesotrophic conditions changed by 166 m and eutrophic conditions by 134 m every year.